Analysis of diurnal variations in body weight of wean-to-finish pigs. (April 2023) - Liu, Zhengxu; Zhang, Xingfu; Ji, Boyu; Banhazi, Thomas; Li, Changchun; Zhao, Shuhong
Abstract : Continuous live weight monitoring can be used to identify optimum marketing weight, production or health problems. In this research we repurposed specialized automatic scales with water and feed supply for experiment, in which body weight (BW) of pigs from wean to finish can be recorded and transmitted. We collected weight data from 62 wean-to-finish pigs from 4 farms over a 3-year period. Twelve of the pigs were Yorkshire pure bred, and the remaining 50 animals were Duroc × Landrace × Yorkshire (DLY) crossbred. After the data was transformed to hourly values; 111, 524 pieces of independent data points were used for the subsequent analysis. In the experimental animals, the average difference between morning and evening BWs was 3.2 kg. The minimum weight in the morning (around 0700–0800h) decreased by 1.7 kg and maximum weight in the evening (around 1800–1900h) increased by 1.5 kg compared with the initial base BW. Furthermore, pigs at older growth stage presented a larger diurnal BW amplitude compared with younger animals. For instance, pigs at the later stage of their life (i.e. >135 kg) experienced an extra 1.5 kg average diurnal reduction in BW when compared to younger pigs (i.e. ≤25 kg). Likewise, older pigs (with BW above 135 kg) increased their body weight daily with an 1.2 kg extra when compared to younger pigs (with BW below 25 kg). Thus, pigs (with BW above 135 kg) had an extra 2.7 kg BW variation compared younger ones (with BW below 25 kg). This study demonstrated that certain level of imprecision has to be accepted when weighing pigs routinely under commercial conditions. The challenge is to use the available data to generate the greatest level of benefits for pig producers while accepting the practically achievable measurement precision. Highlights: The average variation of diurnal body weights of wean-to-finish pig was 3.2 kg. Older pigs showed a larger diurnal body weight amplitude compared with younger ones. Certain imprecision has to be accepted when weighing pigs under commercial conditions.